Pengaruh Pembelajaran/Pengetahuan dan Efisiensi terhadap Modal Manusia, Modal Struktural, Modal Relasional dan Daya Tarik - Nikita Suwan; Alifan Alifan; Justine Tanuwijaya (Universitas Batanghari Jambi, 2022)
Human knowledge is the priority because humans need knowledge in carrying out all activities. This knowledge possessed by humans is one of the capitals they have to manage various activities, especially in an organization or company that has an environment of work needs. Knowledge is intellectual capital and knowledge management is the process of understanding that knowledge. This research method uses a quantitative approach by testing the relationship between each variable. Tests using statistical tests and concluded. The results showed that knowledge and efficiency had a positive effect on human capital, capital structure, relational capital and attractiveness.